Airplane Design Process in the Base of Roskam Method and Application on Design of an Unmanned Air Vehicle - MeharanAli Azizi; Hessam Salehipour; Sima Farazi (International Journal of Advanced Design and Manufacturing Technology, 2008)
In This Article, an unmanned airplane vehicle (UAV) has been design using a new method(Roskam method). This design is based on the maximum payload of 4kg, maximum altitude of  2500m, cruise speed of 120 km/h at sea level and loiter of 60 min. Based on this, desing configuration of the UAV with the aim of patrolling, recognition, and data aquzation, has been done, and design parameters including three - view of airplane is presented.